On Behalf of Creation: Reading the Destructive Cosmic Eschatology of 2 Peter 3 in the Light of the Transfiguration - Neville, David J. (Journal for the study of the New Testament, 2025)
God’s creation of the cosmos is an elemental premise of the New Testament letter known as 2 Peter. Perhaps more overtly than in any other New Testament document, however, 2 Peter anticipates cosmic destruction on the day of divine judgment, when the created order will apparently be subjected to fiery dissolution. As well as looking back to creation and forward to the unpredictable ‘day of the Lord’, 2 Peter also references the historic parousia of Jesus by recalling his transfiguration. Since 2 Peter envisages judgment and salvation as two dimensions of one divine initiative already inaugurated by the historic mission of Jesus, this study looks to the past parousia of Jesus for orientation to his future parousia, both of which are referenced in the letter. This article has a twofold focus: first, destructive cosmic eschatology in 2 Pet. 3 and its potential ecological implications; and second, the hermeneutical value of 2 Peter’s appeal to the transfiguration of Jesus for reflecting on and evaluating 2 Peter’s eschatology—on behalf of creation.